Image-based laparoscopic bowel measurement - Bodenstedt, Sebastian; Wagner, Martin; Mayer, Benjamin; Stemmer, Katherine; Kenngott, Hannes Götz; Müller, Beat P.; Dillmann, Rüdiger; Speidel, Stefanie (International journal of computer assisted radiology and surgery, 2016)
Minimally invasive interventions offer benefits for patients, while also entailing drawbacks for surgeons, such as the loss of depth perception. Thus estimating distances, which is of particular importance in gastric bypasses, becomes difficult. In this paper, we propose an approach based on stereo endoscopy that segments organs on-the-fly and measures along their surface during a minimally invasive interventions. Here, the application of determining the length of bowel segments during a laparoscopic bariatric gastric bypass is the main focus, but the proposed method can easily be used for other types of measurements, e.g., the size of a hernia.